Hydrous hydrazine decomposition over Rh/Al2O3 catalyst: Experimental and CFD studies - Adamou, Panayiota; Bellomi, Silvio; Harkou, Eleana; Chen, Xiaowei; Delgado, Juan J.; Dimitratos, Nikolaos; Manos, George; Villa, Alberto; Constantinou, Achilleas (My University, 2024)
Addressing challenges associated with fossil fuels emissions and contributing to a sustainable energy future is the main objective of the science community. Hydrogen (H2) is emerging as a promising future fuel promoting clean energy production. In this work, the catalytic decomposition of hydrous hydrazine was evaluated using a commercial 0.5 wt% Rh/Al2O3 catalyst for H2 generation. The reaction conditions for the catalyst were optimised in a batch reactor, and computational fluid dynamics (CFD) simulations were performed, accurately validating the results. CFD studies were also conducted on velocity and temperature magnitude and, reactant concentration and catalytic particles distribution in the reactor area, highlighting the key role of the systems’ uniformity on maximum H2 generation. This work is the first, to our knowledge, which uses computational simulation on hydrous hydrazine decomposition, contributing to better understand the reaction kinetics, providing insights for practical hydrogen applications.
Keywords: Batch reactor; CFD; Hydrogen; Hydrous Hydrazine